The Impact of Psychological Skills Training on Performance Enhancement in Athletes: A Meta-analysis - Muhammad Talha (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The basic aim of this research study is to determine the impact of psychological skills training on performance enhancement in athletes. This research study based on the primary research data analysis for this purpose used SPSS software and specific research questions related to indicators, including dependent and independent. Psychological skills training is the main independent variable, and performance enhancement is the main dependent variable. The descriptive statistic analysis, the correlation coefficient, the one-way ANOVA test, and the variance ratio analysis also explain the linear regression analysis between them. PST aids people in cultivating constructive and uplifting self-talk to improve motivation, self-assurance, and attention. PST uses various relaxation methods, including progressive muscle relaxation, deep breathing, and meditation, to lessen anxiety, manage stress, and enhance focus. People need to learn how to stay focused and manage their attention for peak performance. The overall result found that there are positive and significant impacts between psychological skills training and performance enhancement.